Twelve-Month Follow-up of Early COVID-19 Cases in the United States: Cellular and Humoral Immune Longevity. (5th January 2022) - Shah, Melisa M; Rasheed, Mohammad Ata Ur; Harcourt, Jennifer L; Abedi, Glen R; Stumpf, Megan M; Kirking, Hannah L; Tamin, Azaibi; Mills, Lisa; Armstrong, Madeleine; Salvatore, Phillip P; Surasi, Krishna; Scott, Sarah E; et al.
Abstract: We quantify antibody and memory B-cell responses to severe acute respiratory syndrome coronavirus 2 at 6 and 12 months postinfection among 7 unvaccinated US coronavirus disease 2019 cases. All had detectable S-specific memory B cells and immunoglobulin G at both time points, with geometric mean titers of 117.2 BAU/mL and 84.0 BAU/mL at 6 and 12 months, respectively.